Neighbourhood context and unsolved murders: the social ecology of homicide investigations - Petersen, Nick (Policing and society, 2017)
Prior research indicates that victim and crime characteristics shape homicide investigations, yet less is known about the effects of neighbourhood demographics. Drawing upon several theoretical perspectives, this study examines the neighbourhood context of homicide investigations. Multilevel logistic regressions disentangle the effects of covariates at the agency, neighbourhood, and individual level on homicide investigations in Los Angeles County, California. While several non-racial factors influence clearance outcomes, homicides occurring in areas with larger Black and Latino populations are less likely to be cleared. These findings highlight the importance of neighbourhood racial composition beyond victim race effects and have implications for the community context of criminal justice.